Roles of RUNX in B Cell Immortalisation - West,MJ; Farrell,PJ (SPRINGER-VERLAG SINGAPORE PTE LTD, 2017)
RUNX1 and RUNX3 are the main RUNX genes expressed in B lymphocytes. Both are expressed throughout B-cell development and play key roles at certain key developmental transitions. The tumour-associated Epstein-Barr virus (EBV) has potent B-cell transforming ability and manipulates RUNX3 and RUNX1 transcription through novel mechanisms to control B cell growth. In contrast to resting mature B cells where RUNX1 expression is high, in EBV-infected cells RUNX1 levels are low and RUNX3 levels are high. Downregulation of RUNX1 in these cells results from cross-regulation by RUNX3 and serves to relieve RUNX1-mediated growth repression. RUNX3 is upregulated by the EBV transcription factor (TF) EBNA2 and represses RUNX1 transcription through RUNX sites in the RUNX1 P1 promoter. Recent analysis revealed that EBNA2 activates RUNX3 transcription through an 18 kb upstream super-enhancer in a manner dependent on the EBNA2 and Notch DNA-binding partner RBP-J. This super-enhancer also directs RUNX3 activation by two further RBP-J-associated EBV TFs, EBNA3B and 3C. Counter-intuitively, EBNA2 also hijacks RBP-J to target a super-enhancer region upstream of RUNX1 to maintain some RUNX1 expression in certain cell backgrounds, although the dual functioning EBNA3B and 3C proteins limit this activation. Interestingly, the B-cell genome binding sites of EBV TFs overlap extensively with RUNX3 binding sites and show enrichment for RUNX motifs. Therefore in addition to B-cell growth manipulation through the long-range control of RUNX transcription, EBV may also use RUNX proteins as co-factors to deregulate the transcription of many B cell genes during immortalisation.